PENGARUH KEMASAMAN DAN KONSENTRASI ALUMINIUM TERHADAP PERTUMBUHAN BEBERAPA VARIETAS TANAMAN JAGUNG (Zea mays L) - Boer, Dirvamena; Muhidin, Muhidin; Safuan, La Ode (Jurnal Agroteknos, 2011)
This research was conducted in a factorial pattern of split plot design, with three factors. The first factor (as main plot) was acidity (pH), with two treatment levels: pH 4.5 (P1) and pH 6.5 (P2); the second factor (as sub plot) was aluminium concentration, with four treatment levels: 0 ppm Al (A1), 50 ppm Al (A2), 100 ppm Al (A3), and 150 ppm Al (A4); and the third factor (as sub-sub plot) was variety, with eight treatment levels: SU-025 (V1), ST-028 (V2), ST-050 (V3), ST-070 (V4), ST-079 (V5), SE-081 (V6), SE-090 (V7), and SU-094 (V8). Each treatment was repeated twice, resulting in 128 experimental units. The objectives of the research were: (1) to study the effect of acidity, aluminium concentration and their interactions on the growth of several maize varieties, (2) to obtain maize varieties which were tolerant to acidity and high aluminium concentration. Research results showed that acidity influenced leaf area and size. Aluminium influenced stem diameter, leaf area, total leaf weight, plant height, and dry weight of top plant parts (stem and leaves). Variety influenced all growth characters, except leaf size. Interaction between acidity and aluminium concentration influenced seminal root length. Interaction between acidity, aluminium and variety influenced lateral root length, whereas interaction between acidity and variety had no influenced on all plant growth characters. Concentration of 50 ppm Al gave a better effect compared to the concentration of 150 ppm Al. The growth of maize variety ST-028 (V2) and SU-025 (V1) gave a better yield, compared to other varieties. Keywords: acidity, aluminium, maize, in vitro